(untitled) (Research, Society and Development, 2020)
The present study aimed to assess socioeconomic factors associated with breakfast consumption and food intake in children. This is a descriptive and cross-sectional study with a quantitative approach, carried out in a private school with 75 children aged 7 to 10 years of both sexes. For data collection, a socioeconomic questionnaire and a food frequency questionnaire were used. Being stipulated to define the consumption of breakfast, the time at which the meal was taken, before 10 am and for omitting the consumption of breakfast, the frequency between six to no day of the week of consumption of this meal. To assess anthropometric parameters, weight (kg) and height (m) were measured to calculate the Body Mass Index (BMI). The data were tabulated using the Excel® version 2016 program and the results were expressed by means and standard deviations, using the chi-square test or Fisher’s exact test, considering significant p <0.05. The mean age was 104.9 months (SD = 14). The distribution of breakfast consumption was 24% (n = 18) omitting food consumption and 76% (n = 57) consumed it daily, with 72.2% (n = 13) omitting meal among girls and 27.8% (n = 5) in boys. Regarding daily consumption for boys and girls, about 45.6% (n = 26) and 54.4% (n = 31), respectively (p = 0.180). It concludes a hing prevalence of omossion of breakfast consumption among those surveyed.